Studi Komparasi Pemikiran Ekonomi Islam Ibnu Khaldun Dan Ibnu Taimiyah Tentang Mekanisme Pasar - Khermawan, Rizal; , Dr. M. Muhtarom, MH (2016)
Market is an exchange goods and service mechanism which concerned with nature and have been immediately since human courtesy. Islam places marked in the important state in economic state. Market has been get more attention from some classic ulama likes Abu Yusuf, Al-Ghazali, Ibnu Khaldun and Ibnu Taimiyah. Their ideas about market not only give sharp analysis about what happen to human at the moment, but class of futuristic. Ibnu Taimiyah is one of classic ulama who study about market mechanism, such as request mechanism, bargain, balanced market, distortion market and goverment participate in market. Ibnu Taimiyah explains all it on implisit. This is different with Ibnu Khaldun, he only explain request mechanism and bargain mechanism but more clearly and detail. He does not explain other mechanism like Ibnu Taimiyah. The difference and the same ideas of Ibnu Khaldun and Ibnu Taimiyah about market mechanism can know with doing compare analysis (deductive-comparative) to both of these idea's figure. This research purpose to know the consideration of Ibnu Khaldun and Ibnu Taimiyah ideas about market mechanism. According to theoretical this research use to increase knowledge treasure about islamic economy, especially about market mechanism. According to practice this research hope be reference to all civitas academic and agent of economy at all. This research use documentation methods and divining manual included kind of library research. The approach which used is philosophical approach. The result of this research, there are the similarity and diference of ideas between Ibnu Khaldun and Ibnu Taimiyah about market mechanism. Ibnu Khaldun and Ibnu Taimiyah together analyze that increase and decrease factors of good value because pure of market mechanism by nature. Request and bargain as a determining balance value. It does not despotice or unfair factors. The deferences of them are Ibnu Taimiyah according explicit explain about character and function of hisbah institute in Islamic economy. While Ibnu Khaldun does not explain goverment act as special in Islamic economy and all of about market distortion like ba'i najasy, Ihtikār, Talaqqī rukbān, Tagrīr and Tadlīs in his opinion. While Ibnu Taimiyah explains clearly in his book.